Microalgae-based biofertilizer improves fruit yield and controls greenhouse gas emissions in a hawthorn orchard - Ma, Fen; Li, Yingchun; Han, Xue; Li, Kuo; Zhao, Mingyue; Guo, Liping; Li, Shifeng; Wang, Kangjie; Qin, Kangxi; Duan, Jian; Liu, Yutong; Xu, Yuxuan (PLOS ONE, 2024)
Raising attentions have focused on how to alleviate greenhouse gas (GHG) emissions from orchard system while simultaneously increase fruit production. Microalgae-based biofertilizer represents a promising resource for improving soil fertility and higher productivity. However, the effects of microalgae application more especially live microalgae on GHG emissions are understudied. In this study, fruit yield and quality, GHG emissions, as well as soil organic carbon and nitrogen fractions were examined in a hawthorn orchard, under the effects of live microalgae-based biofertilizer applied at three doses and two modes. Compared with conventional fertilization, microalgae improved hawthorn yield by 15.7%−29.6% with a maximal increment at medium dose by root application, and significantly increased soluble and reducing sugars contents at high dose. While microalgae did not increase GHG emissions except for nitrous oxide at high dose by root application, instead it significantly increased methane uptake by 1.5−2.3 times in root application. In addition, microalgae showed an increasing trend in soil organic carbon content, and significantly increased the contents of soil dissolved organic carbon and microbial biomass carbon, as well as soil ammonium nitrogen and dissolved organic nitrogen at medium dose with root application. Overall, the results indicated that the live microalgae could be used as a green biofertilizer for improving fruit yield without increasing GHG emissions intensity and the comprehensive greenhouse effect, in particular at medium dose with root application. We presume that if lowering chemical fertilizer rates, application of the live microalgae-based biofertilizer may help to reduce nitrous oxide emissions without compromising fruit yield and quality.